'It's just like an extra string to your bow': Exploring higher education students' perceptions and experiences of extracurricular activity and employability. (July 2013) - Thompson, Leanne J; Clark, Gordon; Walker, Marion; Whyatt, J Duncan
Students' experience of higher education comprises not only their academic studies but also their extracurricular activities. This article reports on the findings from a mixed-methods research project, exploring in detail the nature and value of extracurricular activity engagement and the significance of institutional schemes encouraging extracurricular activity engagement, from a UK student perspective. Our findings reveal that many students are actively engaged in a variety of extracurricular activities and recognise their value for employability. However, fewer students are strategic in their patterns of involvement, which may be hindered by a lack of career planning. Furthermore, extracurricular activity engagement can be detrimental to academic study, and engagement alone does not assure employability benefits. However, structured institutional schemes encouraging extracurricular activity engagement may facilitate reflection, enabling students to make best use of their experiences for their future careers. Our research contributes to a growing body of research evidence on 'life-wide learning'.